The Role of SIRT3 in the Osteoporosis - Hu, Siwang; Wang, Shuangshuang (Frontiers in Endocrinology, 2022)
SIRT3 is an NAD+-dependent deacetylase in the mitochondria with an extensive ability to regulate mitochondrial morphology and function. It has been reported that SIRT3 participates in the occurrence and development of many aging-related diseases. Osteoporosis is a common aging-related disease characterized by decreased bone mass and fragility fractures, which has caused a huge burden on society. Current research shows that SIRT3 is involved in the physiological processes of senescence of bone marrow mesenchymal stem cells (BMSCs), differentiation of BMSCs and osteoclasts. However, the specific effects and mechanisms of SIRT3 in osteoporosis are not clear. In the current review, we elaborated on the physiological functions of SIRT3, the cell types involved in bone remodeling, and the role of SIRT3 in osteoporosis. Furthermore, it also provided a theoretical basis for SIRT3 as a therapeutic target for osteoporosis.